2017
DOI: 10.1016/j.cub.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Neural Circuits: Reduced Inhibition in Fragile X Syndrome

Abstract: Summary The Drosophila Fragile X Syndrome model has long generated insights into this devastating neurological disease state. A recent study of olfactory neural circuitry shows decreased lateral inhibition onto projection neurons relaying sensory input into higher brain centers causes impaired behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The loss of critical period remodeling in OSNs lacking the Or42a EB odorant receptor indicates that the mechanism requires olfactory reception in the specific OSN, and lateral communication between different OSN classes within the AL is not sufficient to cause remodeling (Acebes et al, 2011(Acebes et al, , 2012Franco et al, 2017;Golovin and Broadie, 2017). The maintenance of OSN critical period remodeling with tetanus toxin blockade does not exclude electrical synapse involvement, which ise not affected by the neurotoxin (Sweeney et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of critical period remodeling in OSNs lacking the Or42a EB odorant receptor indicates that the mechanism requires olfactory reception in the specific OSN, and lateral communication between different OSN classes within the AL is not sufficient to cause remodeling (Acebes et al, 2011(Acebes et al, , 2012Franco et al, 2017;Golovin and Broadie, 2017). The maintenance of OSN critical period remodeling with tetanus toxin blockade does not exclude electrical synapse involvement, which ise not affected by the neurotoxin (Sweeney et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This is a very important consideration because AL lateral connections from other activated olfactory sensory neurons could possibly affect VM7 critical period development. Indeed, recent work has demonstrated that altered lateral inhibition in the AL can modulate olfactory sensory processing and change olfactory behavioral outputs (Acebes et al, 2011(Acebes et al, , 2012Franco et al, 2017;Golovin and Broadie, 2017). We therefore tested whether the specific activation of Or42a receptors is required for critical period synaptic remodeling of Or42a OSNs within the VM7 glomerulus.…”
Section: Or42a Olfactory Reception Is Required For Critical Period Rementioning
confidence: 94%
“…In animal models of TCD, hyperpolarization of thalamic relay neurons has been observed to lead to alterations in firing patterns of low-threshold calcium spikes which are reflected in local field potentials as elevated theta rhythmicity(Jeanmonod et al, 1993; Jeanmonod et al, 2003; Llinás et al, 1999). A dominant theta rhythm may be reflective of a diminished inhibitory capacity at a systems-level resulting in excess asynchronous gamma activity and the so-called gamma “edge effect” (Golovin & Broadie, 2017; Llinás et al, 1999; Paluszkiewicz et al, 2011; R et al, 2005).…”
Section: Introductionmentioning
confidence: 99%